Effects of Fracturing Parameters on Fracture Unevenness During Large-Stage Multi-Cluster Fracturing in Horizontal Wells - Yong, Rui; Zhou, Fu-Jian; Li, Ming-Hui; Song, Yi; Zhou, Xiao-Jin; Zhao, Zhi-Heng; Li, Ben; Qin, Shi-Yong (Frontiers in Energy Research, 2021)
Horizontal wellswith multi-cluster fracturing technology is an effective approach to exploit unconventional hydrocarbon reservoirs. The on-site diagnosis results indicate that multi-cluster fractures always tend to propagate unevenly due to stressinterference, therefore it is very essential to study the effect of fracturing parameters on fracture propagation unevenness. In this paper, the unconventional fracturing model (UFM, Unconventional Fracturing Model) is used to study the effect of multi-cluster fracturing parameters on fracture unevenness in a large stage. This model has been validated with the actual fracturing case on-site in the Longmaxi shale. The investigated parameters include completion parameters (cluster spacing, number of perforations per cluster), pumping parameters (fluid injection intensity and proppant injection intensity). Our simulation results show that firstly reducing fracture spacing will increase stress interference, andhydraulic fractures exhibit a “radial” pattern. Secondly, reducing the perforation number of a single cluster can promote the more uniform propagation of multi-cluster fractures. Thirdly, increasing the fluid injection intensity will increase the fracture length, but will also increase the fracture unevenness. Besides, the injection strength of the proppant has a little effect on the average fracture length and the unevenness of the fracture length. Finally, setting a reasonable cluster spacing and injection fluid strength can obtain a more uniform fracture propagation. Meanwhile reducing the number of perforations per cluster can also reach the goal of propagating evenly. This paper provides a certain reference for the optimization of multi-cluster fracturing parameters in large-stage and multi-cluster wells.